Factors associated with burnout in Polish healthcare workers during the COVID-19 pandemic - Holas, Paweł; Wojtkowiak, Natalia; Gambin, Małgorzata; Hansen, Karolina; Kmita, Grażyna; Pisula, Ewa; Bargiel-Matusiewicz, Kamilla; Łojek, Emilia (Frontiers in Public Health, 2023)
The Covid-19 pandemic has placed the healthcare system under substantial strain that has caused elevated psychological distress among healthcare workers (HCWs). Previous studies have found a high prevalence of burnout among HCWs exacerbated by the COVID-19 pandemic and have delineated some associated factors, but further research is needed. Little is known, for example, whether the economic status of HCWs or experiencing negative and positive emotions contribute to burnout. The present study was meant to fill this gap. A total of 412 HCWs (i.e.: nurses - 47%, physicians - 28%, psychologists - 14%, and other healthcare professionals - 11%), aged 21 to 69 years (M = 36.63; SD = 11.76) participated in a web-based cross-sectional study. Data was collected from June to November 2020. The participants filled out measures assessing two dimensions of burnout (Exhaustion and Disengagement), depression, generalised anxiety, positive and negative emotions, along with the survey evaluating organizational aspects of their work during the pandemic. Burnout thresholds were met by 54% and 66% of respondents for Disengagement and Exhaustion, respectively, which is high but comparable to levels found in other countries during the pandemic. Similarly to previous work, depression and anxiety were high in HCWs, with 24 % of them being in the risk group for clinical severity of depression and 34% in the risk group for a clinical generalised anxiety disorder (GAD). Regression analysis showed that the intensity of negative emotions was the strongest predictor of Exhaustion, whereas the intensity of positive emotions was the strongest predictor of Disengagement. Depression and GAD symptoms were positively related to Exhaustion, and economic status was inversely related to Disengagement. These results suggest that distress in HCWs during the pandemic was related to symptoms of burnout, whereas higher income and experiencing positive emotions were associated with reduced burnout levels. Our findings call for the development of burnout intervention programs that could build capacities for dealing with depression and other negative emotions and at the same time teach skills on how to increase positive emotions in HCWs.